2021
DOI: 10.1177/0011128721999342
|View full text |Cite
|
Sign up to set email alerts
|

Examining Trauma and Crime by Gender and Sexual Orientation among Youth: Findings from the Add Health National Longitudinal Study

Abstract: LGBTQ youth, and in particular those of color, are significantly more at risk for experiencing trauma at home and in their community, having school difficulties including bullying and suspensions, and subsequently being involved with the juvenile and criminal justice systems. Research is limited in understanding the pathways these young people take toward youthful and young adult offending and incarceration. The national longitudinal Add Health study data were used to explain how trauma, sexual orientation (ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Dependent variables in this study included self-reported measures of four adult criminal outcomes, all of which were measured at Wave V. Violent offending was measured based on whether or not (0 = “ no” , 1 = “ yes” ) the respondents engaged in the following three offenses in the past 12 months: (1) getting into a serious physical fight, (2) pulling a knife or gun on someone, and (3) shooting or stabbing someone. Due to the high positive skewness in the distribution, lack of variability in the summative measure of violent offending, and following previous studies (Farrell et al, 2018; Yun et al, 2022), the measure was dichotomized, with respondents who reported engaging in at least one of these offenses assigned a value of “1”. Non-violent offending was measured based on whether (0 = “ no ”, 1 = “ yes ”) the respondents reported engaging in the following offenses in the past 12 months: (1) stealing something worth more than $50, (2) illegally selling drugs, and (3) deliberately damaging property.…”
Section: Methodsmentioning
confidence: 99%
“…Dependent variables in this study included self-reported measures of four adult criminal outcomes, all of which were measured at Wave V. Violent offending was measured based on whether or not (0 = “ no” , 1 = “ yes” ) the respondents engaged in the following three offenses in the past 12 months: (1) getting into a serious physical fight, (2) pulling a knife or gun on someone, and (3) shooting or stabbing someone. Due to the high positive skewness in the distribution, lack of variability in the summative measure of violent offending, and following previous studies (Farrell et al, 2018; Yun et al, 2022), the measure was dichotomized, with respondents who reported engaging in at least one of these offenses assigned a value of “1”. Non-violent offending was measured based on whether (0 = “ no ”, 1 = “ yes ”) the respondents reported engaging in the following offenses in the past 12 months: (1) stealing something worth more than $50, (2) illegally selling drugs, and (3) deliberately damaging property.…”
Section: Methodsmentioning
confidence: 99%
“…Some LGBTQ students report being pushed out of the classroom environment because of a hostile school climate, which includes bullying, verbal abuse, and threats, among others (Majd, Marksamer, & Reyes, 2009; Mitchum & Moodie‐Mills, 2014). These experiences increase the risk for absenteeism, truancy, poor peer choices, among other impacts, and can lead to increased delinquent behaviors and juvenile detention, all significant risks for involvement in the adult criminal justice system (Yun, Fukushima‐Tedor, Mallett, Quinn, & Quinn, 2021). Once involved with the courts, young people are significantly more likely to remain involved and to recidivate (Cohen et al, 2014; Petrosino, Turpin‐Petrosino, & Guckenburg, 2010).…”
Section: Impact On Students Discipline and School Environmentsmentioning
confidence: 99%
“…Schools that employ SROs have the challenge of moving toward inclusive and pro‐social school climate interventions such as restorative justice and positive behavioral protocols, when it is often the presence of SROs that impedes this process for many at‐risk students, depending on school type, student body make up, and other factors (Pigott, Stearns, & Khey, 2018; Weisburst, 2018). The young people disproportionately impacted by the SRO presence – students of color, students with disabilities, and students who identify as LGBTQ ‐ are already excluded from school more often, victimized, and/or are on pathways to the juvenile justice system (U.S. Department of Education, 2019; Yun et al, 2021). This is a difficult paradox.…”
Section: Effective School Approachesmentioning
confidence: 99%